2015
DOI: 10.3892/ol.2015.3344
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia promotes C-X-C chemokine receptor type 4 expression through microRNA-150 in pancreatic cancer cells

Abstract: Abstract. Hypoxia promotes pancreatic cancer progression by triggering cancer cell invasion. However, the mechanism underlying this process remains unclear, hindering the development of effective therapies. The present study aimed to delineate the molecular mechanisms underlying the prometastatic effect of hypoxia in pancreatic cancer cells. The expression of microRNA-150 (miRNA-150) was detected using reverse transcription-quantitative polymerase chain reaction in pancreatic cancer samples and in the hypoxia-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Figure 3 depicts the effects of microenvironmental remodeling on PC progression under hypoxic conditions. [104] miR-142 Down miR-142-HIF-1α-vimentin, VEGF-C, E-cadherin Inhibits proliferation, EMT, and invasion [184] miR-150 Down miRNA-150-CXCR4 Inhibits migration and invasion [185] miR-519 Down miR-519-PD-L1 Inhibits cell invasiveness, and induces apoptosis [186] miR-548an Down HIF-1α-HDAC1-miR-548an-vimentin Inhibits the proliferation and invasion [187] Pathological angiogenesis under hypoxia…”
Section: Emt Invasion Migration and Metastasis Under Hypoxiamentioning
confidence: 99%
“…Figure 3 depicts the effects of microenvironmental remodeling on PC progression under hypoxic conditions. [104] miR-142 Down miR-142-HIF-1α-vimentin, VEGF-C, E-cadherin Inhibits proliferation, EMT, and invasion [184] miR-150 Down miRNA-150-CXCR4 Inhibits migration and invasion [185] miR-519 Down miR-519-PD-L1 Inhibits cell invasiveness, and induces apoptosis [186] miR-548an Down HIF-1α-HDAC1-miR-548an-vimentin Inhibits the proliferation and invasion [187] Pathological angiogenesis under hypoxia…”
Section: Emt Invasion Migration and Metastasis Under Hypoxiamentioning
confidence: 99%
“…Chronic hypoxia increases the expression of CXCR4 in tumor cells such as breast cancer cells ( Figure 4 ) [ 233 , 234 , 235 , 236 , 237 , 238 ], chondrosarcoma cells [ 239 , 240 ], clear cell-renal cell carcinomas cells [ 223 ], chronic lymphocytic leukemia [ 241 ], colon cancer cells [ 62 , 242 , 243 ], gastric cancer cells [ 212 , 244 ], glioblastoma multiforme cells [ 226 , 245 , 246 , 247 ], GOT1 cells (ileal carcinoids) [ 221 ], lung cancer cells [ 248 , 249 ], melanoma cells [ 250 , 251 ], multiple myeloma cells [ 252 ], oral squamous cell carcinoma cells [ 253 ], osteosarcoma cells [ 254 , 255 ], pancreatic ductal adenocarcinoma cells [ 256 , 257 ], renal cell carcinoma cells [ 258 ], and retinoblastoma cells [ 259 ]. However, chronic hypoxia does not universally induce CXCR4 expression in tumor cells—for example, in hepatocellular carcinoma cells it only increases the expression of CXCR4 in some cell lines [ 260 ].…”
Section: Effect Of Hypoxia On the Expression And Function Of Cxcl1mentioning
confidence: 99%
“…In breast cancer cells, chronic hypoxia increases CXCR4 expression independently of HIF-1, depending only on NF-κB [ 233 ]. Chronic hypoxia increases the expression of CXCR4 in the pancreatic ductal adenocarcinoma cell line by reducing the level of miRNA-150 [ 257 ]. In chondrosarcoma, chronic hypoxia increases the expression of miRNA-181a, which controls the expression of the regulator of G-protein signaling 16 (RGS16) [ 240 , 268 ].…”
Section: Effect Of Hypoxia On the Expression And Function Of Cxcl1mentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo experiments also demonstrated the relationship between UV exposure and the downregulation of miR-155-5p in the development of squamous cell carcinoma (SCC) [ 25 , 26 ]. Furthermore, in vitro studies have shown that miR-150-5p is downregulated by hypoxia in pancreatic cell lines [ 27 ]. Nevertheless, the above-mentioned miRNAs have been described as favorable biomarkers in skin melanomas or as tumor suppressor miRNAs [ 9 , 14 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%